Peran Bimbingan dan Konseling Dalam Membangun Kepercayaan Diri Anak Di Desa Gayam - Nurhayati; Anis Tri Yuliana, M,Pd. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of counseling in building children's self-confidence in Gayam Village, Sumenep Regency. Using field research with a qualitative descriptive approach, data were obtained through observations and interviews with the village head, community leaders, and children in Gayam Village. The results indicate that counseling plays a crucial role in helping children understand their potential, develop communication skills, develop positive mindsets, and encourage active participation in social activities. Factors influencing low self-confidence include low education levels, an unsupportive social environment, limited access to information, and poorly controlled social interactions. Strategies implemented in the counseling service include group discussions and public speaking simulations, conducted in stages to build children's confidence. These findings confirm that structured and ongoing counseling can increase children's self-confidence, encourage social engagement, and shape a younger generation that is more courageous, optimistic, and ready to face challenges.